The Value of Prenatal First Systolic Blood Pressure Can Predict Severe Preeclampsia and Birth Weight in Patients With Preeclampsia - Gan, Bei; Wu, Xiuyan; Lu, Lin; Li, Xuemei; Li, Jianhua (Frontiers in Medicine, 2022)
Background Preeclampsia is a serious complication of pregnancy that threatens the safety of the fetus and mother. We assessed the relationship between systolic blood pressure (SBP) in the early pregnancy stage (12 weeks) in patients with preeclampsia and the development of severe eclampsia and birth weight. Methods Patients were categorized based on the quartiles of the prenatal first SBP level. Logistic regression analysis was performed to assess whether prenatal first SBP was a risk factor for low birth weight and severe preeclampsia. The area under the receiver-operating characteristic curve (AUC) of sensitivity and specificity were used to predict the risk of low birth weight and severe preeclampsia. Results A total of 333 patients with preeclampsia were enrolled. There were 162 (48.6%) patients with severe preeclampsia and 270 (81.08%) cesareans. Group I patients with a prenatal first SBP ≤ 119 mmHg prenatal had a higher birth weight. Multiple logistic regression analysis showed that serum creatinine (p = 0.025), prenatal first SBP (p = 0.029), S-preeclampsia (p = 0.003), gestational age (p < 0.001), total cholesterol (TC) (p < 0.001), and low-density lipoprotein (LDL) (p < 0.001) were independent risk factors for low birth weight. Multiple logistic regression analysis showed that prenatal first SBP (p = 0.003), TC (p = 0.002), and B-type natriuretic peptide (BNP) (p < 0.001) were independent risk factors for severe preeclampsia. Compared with Group I (SBP ≤ 119 mmHg), the incidence of low birth weight for patients in groups III (131 ≤ SBP ≤ 138 mmHg) and IV (SBP ≥ 139 mmHg) was significantly higher. Even after correcting for age, gestational age, and biochemical indices, the difference remained statistically significant. The risk of diagnosed severe preeclampsia for patients in Groups IV (SBP ≥ 139 mmHg), III (131 ≤ SBP ≤ 138 mmHg), and II (120 ≤ SBP ≤ 130 mmHg) was significantly higher than that in Group I (SBP ≤ 119 mmHg). The AUC of the prenatal first SBP for predicting low birth weight and severe preeclampsia was 0.676 (95% CI 0.618–0.733, p < 0.001) and 0.727 (95% CI 0.673–0.781, p < 0.001), respectively, in patients with preeclampsia. Conclusions Prenatal first SBP was associated with birth weight and severe preeclampsia. Higher prenatal first SBP in patients with preeclampsia can predict low birth weight and severe preeclampsia.